"Once upon a time, there was a fairy who walked in paradise": the child finalised, mediated and creative narrative activity. (1st January 2014) - Decortis, Françoise; Bationo-Tillon, Anne
The research on children storytelling is dominated by approaches that focus on contents, structure and process of narrative storytelling. We propose a change of paradigm that considers the narrative activity in its finalised, situated, mediatised and creative properties. To do it we focus on several theoretical contributions stemming from activity theories, instrumental approach, the cycle of the creative activity of imagination and the transitional zone of experience (Vygotsky, Rabardel, Winnicott). The narrative activity model generated from these theoretical contributions is grounded on empirical researches conducted with children from six to eight years old. It includes four phases, exploration, inspiration, production and sharing. We show the usage of instruments that the children make in these four phases. Indicators stemming from a typology of transitional instruments and from several forms of narrative activities (linear, spiral, editing, sieving) are used to refine our conceptualisation of the narrative activity as mediated activity.